Exploring Nurse Manager Support of Evidence-Based Practice: Clinical Nurse Perceptions. (May 2018) - Caramanica, Laura; Spiva, LeeAnna
Abstract : OBJECTIVE: The study identifies what constitutes nurse manager (NM) support and other resources that enable clinical nurses (CNs) to engage in evidence-based practice (EBP). BACKGROUND: Clinical nurses report that NM support enables them to use EBP but what constitutes NM support is still unclear. METHODS: Nurse managers, CNs, and EBP mentors received specialized education and use a team approach for EBP. Data were collected preintervention, mid-intervention, and postintervention from observations, interviews, journaling, and surveys. RESULTS: Results demonstrate how NMs can perform their role responsibilities and still engage CNs to develop a spirit of inquiry, seek answers to their clinical questions using EBP, and advance their clinical performance to improve patient outcomes. Four NM supportive behaviors emerged: cultivating a shared EBP vision, ensuring use of EBP, communicating the value of EBP, and providing resources for EBP. CONCLUSION: Through education and support, NMs describe supportive behaviors necessary for the successful conduction of EBP by CNs.